Projeto pedagógico e estrutura curricular de um curso de odontologia: análise crítica fundamentada na percepção acadêmica - Moimaz, Suzely Adas Saliba [UNESP]; Fadel, Cristina Berger; Bino, Livia da Silva [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2010)
Considering that the current pedagogical project for the Dentistry course at FOA-Unesp was structured in 2001, a year before the national resolution that introduced the new curricular guidelines for the dental field, the aim of this study was to analyze critically this document and assess the academic perception of the pedagogical project, as well as the current curricular structure. A previously tested and validated semi-structured questionnaire was used to obtain the needed information, and a documentary analysis was conducted. The questionnaire was drafted based on data from the National Curricular Guidelines (DCN) and Unified Health System (SUS) guidelines. The sample consisted of almost all the graduating students of 2007 (n = 61). Of these, 95% had no knowledge of the pedagogical project for the undergraduate course; 53% found the integration between the disciplines offered by the course insufficient; 66% pointed out that there was duplication of the revised contents; 41% said that the interdisciplinary relation was unsatisfactory, and 67.2% said they preferred the modular system of teaching. Furthermore, 55.7% of the students said that that the course does not fully cover the principles of completeness and resolution of actions, and 37.7% pointed out that clinical care was not humanized. As for the competence and skills needed to exercise the profession, the students admitted feeling secure about carrying out preventivecurative clinical actions, and feeling insecure about developing broad ranging actions, like managing and planning. Analysis of the documents showed a certain disagreement in the organization of the pedagogical project and the curricular structure, when confronted with the course of action set down by the National Curricular Guidelines. The data prove the urgent need to restructure the FOA-Unesp curriculum and confirm the importance of a continuous evaluation in higher education.

Considerando-se que o projeto pedagógico vigente do curso de graduação de Odontologia da FOAUnesp foi formulado em 2001, ano anterior à resolu- ção nacional que instituiu as novas Diretrizes Curriculares para a área odontológica, objetivou-se realizar a análise crítica desse documento e avaliar a percepção acadêmica, quanto ao projeto pedagógico e à estrutura curricular vigentes. Para a obtenção das informações, além de análise documental, utilizou-se um questionário semi-estruturado, elaborado com base em dados constantes nas DCN e nas diretrizes do SUS, previamente testado e validado. A amostra constituiu-se de 92,4% de formandos de 2007 (n = 61). Destes, 95% não conheciam o projeto pedagógico que estrutura o curso de graduação; 53% consideraram insuficiente a integração entre as disciplinas ofertadas pelo curso; 66% apontaram que havia duplica- ção de conteúdos trabalhados; 41% disseram que a relação interdisciplinar era insatisfatória e 67,2% optariam pelo sistema modular de ensino. Ainda, 55,7% dos acadêmicos afirmaram que o curso não contempla totalmente os princípios da integralidade e resolutividade das ações, e 37,7% ressaltaram que o atendimento clínico não era humanizado. Quanto às competências e habilidades necessárias ao exercício da profissão, os acadêmicos admitiram sentir seguran- ça para realizarem ações clínicas preventivo-curativas e demonstraram insegurança para desenvolverem ações amplas, como as gerenciais e de planejamento. A análise documental indicou certo desacordo na organização do projeto pedagógico e da estrutura curricular, quando confrontados com as vertentes pautadas pelas Diretrizes Curriculares Nacionais. Os dados comprovam a urgente necessidade de reformulação curricular da FOA-Unesp e confirmam a importância da avaliação contínua no ensino superior.
Pedagogical project and curricular structure in a dentistry course: critical analysis based on academic perception
Keywords: Higher education; Teaching; Dentistry; Educação superior; Ensino; Odontologia